Download presentation

Presentation is loading. Please wait.

Published byMarvin Strickland Modified over 5 years ago

1
Algebra II Honors Properties Review Chapter 1

2
We will solve 2x + 4 = 6x – 12 Showing all of the properties used So Let’s go!

3
2x + 4 = 6x – 12 2x + 4 = 6x - 12 +(-6x) Addition Property of equality Subtract 6x from both sides

4
2x + 4 +(-6x) = 6x 2x + (-6x) + 4 = 6x - 12 + (-6x) + (-6x) -12 Commutative Property of Addition Move like terms together

5
2x + 4 + (-6x) = - 12 2x + 4 + (-6x) = 6x + (-6x) - 12 0 Additive Inverse Property Add opposites

6
2x + 4 +(-6x) = 2x + 4 + (-6x) = 0 - 12 -12 Addition/ Subtraction Property Of Zero Add 0 to -12

7
2x + = - 12 (-6x) + 4 Commutative Property of Addition 2x + 4 + (-6x) = - 12 Move like terms together

8
+ 4 = -12 2x + (-6x) + 4 = - 12 [2 + (-6)] x Distributive property of Addition over Multiplication Factor out the “x”

9
x + 4 = -12 [2 + (-6)] x + 4 = -12 (-4) Substitution Property of Equality Add real numbers together

10
-4x + 4 = -12 + (-4) Addition Property of Equality Subtract 4 from both sides

11
- 4x + = -12 + (-4) -4x + 4 + (-4) = -12 + (-4) (4 - 4) Associative Property of Addition Change order of operations by grouping

12
-4x + = -12 + (-4) -4x + (4 - 4) = -12 + (-4) (0) Additive Inverse Property Add opposite terms

13
= -12 + (-4) -4x + 0 = -12 + (-4) -4x Addition Property of Zero Add zero to a number

14
-4x = -16 -4x = -12 + (-4) Substitution Property of Equality Combine real numbers

15
(-4x) = (-16) -4x = -16 (-1/4) Multiplication Property of Equality Multiply both sides by (-1/4)

16
= (-1/4 )(-16) (-1/4)(-4x) = (-1/4)(-16) (-1/4*-4)x Associative Property of Multiplication Change order of operations by grouping

17
x = -1/4 (-16) (-1/4*-4)x = -1/4 (-16) 1 Multiplicative Inverse Property Multiply opposites

18
= -1/4 (-16) 1x = -1/4 (-16) x Multiplicative Identity Property Multiply by 1

19
x = x = -1/4 (-16) 4 Substitution Property of Equality Multiply real numbers together

20
2x + 4 = 6x – 12 2x + 4 + (-6x) = 6x – 12 + (-6x) 2x + 4 + (-6x) = 6x + (-6x) - 12 2x + 4 +(-6x) = 0 - 12 2x + 4 + (-6x) = -12 2x + (-6x) + 4 = -12 [2 + (-6)] x + 4 = -12 -4x + 4 = -12 -4x + 4 + (-4)= -12 + (-4) -4x + (4 - 4) = -12 + (-4) -4x + (0) = -12 + (-4) -4x = -12 + (-4) -4x = -16 (-1/4) (-4x) = (-1/4 )(-16) (-1/4*-4)x = (-1/4) (-16) 1x = -1/4 (-16) x = -1/4 (-16) x= 4 Properties Step by Step Addition Prop. of Equality Commutative Prop. of Addition Additive Inverse Property Addition Prop. of Zero Commutative Prop. of Addition Distributive Property Substitution Property Addition Property of Equality Associative Property of Addition Additive Inverse Addition Property of Zero Substitution Property Multiplication Prop. of Equality Association Prop. of Multiplication Multiplicative Inverse Multiplicative Identity Substitution

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google